A theory-based discussion of international technology funding - Michael Hübler (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2014)
Climate policy negotiations identi ed international technology funding as a means of achieving carbon emissions reductions in developing countries. Such funds are now being realized. This paper is probably the first theory-based discussion of international technology funding. It sets up a Ramsey model of a developing economy including imports of capital and embodied technologies from abroad. Going beyond a scale, technique and composition effect, it disentangles five resulting economic effects and four technology-related policy levers and their interactions. It then discusses their role in designing an international technology fund with the aim to reduce emissions effciently. The paper concludes that it is ineffcient to address emissions reductions independent of the technological absorptive capacity and other aspects of economic development. Therefore, it opts for an integrated technology funding scheme.
Keywords: F21; O11; O33; O47; 330; technology fund; climate policy; economic development